Consumer Perception towards Social Media Marketing in Kathmandu - Sah, Gunja Kumari (Patan Pragya, 2022)
Social media advertisement has a great influence on the consumer's perception. The research aims to understand the perception of customers toward social media marketing. Customers consider Facebook the finest social media, preferring it to Youtube, Whatsup, Instagram, and Tiktok for its interesting social media advertisements. Businesses and digital marketers require a deep understanding of how consumers interact with social media marketing to appreciate the consumer view of social media truly. The research goals were accomplished using a descriptive research methodology. The research sample was composed of 250 Kathmandu valley residents utilizing convenience sampling. It demonstrated that most respondents concurred that social media marketing offered consumers enough information. The least responders disagreed that the information wasn't clear and ineffective. However, the majority of respondents agreed that social media advertisements provide adequate information to customers.